Klasifikasi Citra Warna Daun Padi Menggunakan Metode Histogram of S-RGB dan Fuzzy Logic Berbasis Android - Raimundus Sedo; Panca Mudjirahardjo; Erni Yudaningtyas (Universitas Islam Sumatera Utara, 2019)
The level of greenish leaves of rice plants is one indicator to analyze the nutrient needs of the rice plant nitrogen required. In the process, one recommended way to determine nitrogen needs for the rice plant is the use Leaf Color Chart (LCC). Given the need for efficiency of time and energy, and to avoid the perception of the color differences are observed, it is important to do the development of a system to facilitate the farmers in determining the nitrogen requirements for rice.This research aims to develop an Android-based system to determine nitrogen needs for the rice crop through image processing concept. The method used is of s-RGB Histograms and Fuzzy Logic. Method of s-RGB Histogram function to extract the characteristic color of rice leaves, while Fuzzy Logic is used to classify images based on 4 levels of rice leaf color on the LCC also to determine the dose of nitrogen necessary for the needs of rice plants.Tests carried out using Samsung's smartphone brands with a capacity of 8 MP camera. The test results and evaluation system using the Confusion Matrix for Multiple Classes showed that the accuracy of the system provide the requested information is considered good enough, that is 88.19%. The success of the system to find the information back to the recall level of 88.25%. Degree of proximity between the predicted value of the system to the actual value of 88.75%, and the level of specificity obtained at 62.12%. While the system achieved computational time average of 10:14 seconds. Keywords- Histogram of s-RGB, Fuzzy Logic, Leaf Color Chart, Confusion Matrix for Multiple Classes